K-State Libraries Usability Team report: self-checkout machine mini test - Duever, Meagan; Coleman, Tara L.; Logan, Cindy; Devlin, Marjorie (Kansas State University. K-State Libraries, 2015)
K-State Libraries employs a patron-centered approach to information finding and resource sharing that makes our online and physical presence easy to navigate, sought out by patrons, valid in content, and reliable in currency of information. The primary outcome of this usability test was to determine the optimal placement of two self-checkout machines on the main floor of Hale Library, the campus’ largest library. This test was conducted during the summer of 2014 and, again at mid-fall of the same year when checkout totals were the greatest. We found that the majority of patrons who participated in the test had used the self-checkout machines before, or were at least aware of their availability in Hale Library. Heat maps were created from survey feedback to identify the preferred locations for the two self-check machines.
Keywords: K-State Libraries; Circulation; Usability; Access services; Self-checkout machines